Assessing Phenonip™ antimicrobial agent degradation through electrochemical processes with DSA® and BDD anodes - de Mello, Rodrigo [UNESP]; de Jesus, Renan Nakamura; Motheo, Artur J. (Springer Nature, 2025)
The growing concern regarding contamination from pharmaceuticals, cosmetics, and personal care products highlights the urgent need to address this significant environmental and public health challenges. Parabens are widely used as preservatives. Its use is already prohibited in Europe and the USA but remains permitted in Brazil. Even at low concentrations, parabens pose risks to human health, the environment, and animals. Ineffective water resource management and the limitations of traditional effluent treatment methods intensify this issue. This study investigated the potential of electrochemical and photo-assisted electrochemical technologies in degrading Phenonip™, an industrial preservative composed of a mixture of parabens and phenoxyethanol. Two types of commercial anodes were employed: boron-doped diamond (BDD) and the Dimensionally Stable Anode (DSA®). The efficiency of these processes was assessed in relation to applied current density, with monitoring of organic carbon levels, contaminant concentrations, energy consumption, and pH. As expected, the time required for complete removal of all contaminants from the sample decreased with higher current densities. However, at elevated current densities, a noticeable increase in energy consumption was observed. In the case of the photo-assisted electrochemical system, an interesting trend emerged: energy consumption decreased as current density increased, attributed to the significantly shorter time needed for complete contaminant removal compared to the traditional electrochemical process. Furthermore, a significant shift in the kinetic behavior of these compounds removal was observed once nearly 80% of the parabens were removed, indicating an alteration in the rate-limiting step or reaction mechanism of the degradation process. These results provide valuable insights into the potential applications of these innovative methods in addressing the urgent challenge of removing contaminants from industrial effluents.
Keywords: Advanced eletrochemical technology; Boron-doped diamond anode; Emerging pollutants removal; Mixed metal oxide anode; Paraben degradation strategy